Overcoming Critical Constraints to Sustaining Productivity Growth in Key Commodities of Asia and the Pacific - Mercedita Sombilla; Dennis Mapa; Sharon Piza (Asian Development Bank (ADB), 2013)
Two trends on yields have been observed for rice, wheat, and even edible oils in Asia. The deceleration of yield growth is one of these trends. The other relates to the differential yield increases across countries in the region. This study provides explanations for both trends and relates these to the exhaustion of the yield potential of current technology, emerging threats posed by climate change and other disturbances, varying levels of development across countries and hence the development of infrastructure, among others. Total factor productivity (TFP) estimates for these commodities indicate the potential to overcome these constraints, however. Key determinants of TFP growth were identified and discussed. While the influence of these determinants on the TFP estimates was not tested empirically in this study because of data limitations, evidence of the relationship was clear and strong in numerous TFP studies done for the agriculture sector as a whole, and for rice and wheat in various countries including Asian countries. Long-term growth will have to come from great advances in interventions being undertaken, three of which include (i) major breakthroughs in new varieties and farming systems in both fertile and unfertile lands; (ii) the restructuring of small farms into more efficient, mechanized large-scale operations, especially in production areas with good infrastructure for market access and irrigation; and (iii) the development of market mechanisms to enhance the comparative advantage of domestic production and explore the value-adding potential of commodities, particularly edible oil. Three policy recommendations are also forwarded to achieve these great advances: (i) sustained investment in agriculture; (ii) getting the mix of institutions right; and (iii) gearing up for globalization. The role of development partners as well as the private sector in effecting sustainable growth is briefly discussed as a concluding section.
hdl:11540/2074
Keywords: D24; D57; O13; Q11; Q18; 330; TFP; constraints; Asia Pacific; rice; wheat; edible oil; investment; institutions; globalization; private sector; development partners